2017
DOI: 10.4038/gmj.v22i1.7958
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of elders in Galle district, Sri Lanka

Abstract: Introduction: Geriatric population in Sri Lanka is a potentially vulnerable group for malnutrition. The present study was carried out to assess the nutritional status of elderly in Galle and to identify the relationships of their nutritional status with gender, age, area of residence, level of education and income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Of the socio-demographic factors, age ≥ 70 years was significantly associated with low skeletal muscle mass and high fat mass among the older women in the present study. Age consistent findings for these associations were reported in descriptive studies conducted among the older people of ≥60 years reported in Galle [ 30 ] and Kandy district [ 12 ] where advancing age was significantly associated with undernutrition.…”
Section: Discussionsupporting
confidence: 85%
“…Of the socio-demographic factors, age ≥ 70 years was significantly associated with low skeletal muscle mass and high fat mass among the older women in the present study. Age consistent findings for these associations were reported in descriptive studies conducted among the older people of ≥60 years reported in Galle [ 30 ] and Kandy district [ 12 ] where advancing age was significantly associated with undernutrition.…”
Section: Discussionsupporting
confidence: 85%
“…Elderly people are more susceptible to nutritional problems arising from issues with the body's digestion and absorption mechanisms, which deteriorate as part of the natural aging process (HRCSL and Helpage Sri Lanka 2014). The elderly population is also more susceptible to malnutrition, and a recent study revealed that 30 percent of institutionalized elderly in Sri Lanka were malnourished (De Silva et al 2017). Overweight or obesity in elders is also a concern, and obesity in elderly women has been recorded at 60 percent, whereas obesity in elderly men was 43.8 percent (De Silva et al 2017).…”
Section: Population Aging and Challenges To Health Carementioning
confidence: 99%
“…The elderly population is also more susceptible to malnutrition, and a recent study revealed that 30 percent of institutionalized elderly in Sri Lanka were malnourished (De Silva et al 2017). Overweight or obesity in elders is also a concern, and obesity in elderly women has been recorded at 60 percent, whereas obesity in elderly men was 43.8 percent (De Silva et al 2017). According to WHO, this dual burden of nutrition has a major impact on the aging process and on the morbidity and mortality of the elderly population.…”
Section: Population Aging and Challenges To Health Carementioning
confidence: 99%
“…Elderly people are more susceptible to nutritional problems arising from issues with the body's digestion and absorption mechanisms, which deteriorate as part of the natural ageing process (HRCSL and Helpage Sri Lanka 2014). The elderly population is also more susceptible to malnutrition, and a recent study revealed that 30 percent of institutionalized elders in Sri Lanka were malnourished (De Silva et al 2017). Overweight or obesity in elders is also a concern, and obesity in elderly women was recorded at 60 percent while obesity in elderly men was 43.8 percent (De Silva et al 2017).…”
Section: Population Ageing and Challenges To Health Carementioning
confidence: 99%
“…The elderly population is also more susceptible to malnutrition, and a recent study revealed that 30 percent of institutionalized elders in Sri Lanka were malnourished (De Silva et al 2017). Overweight or obesity in elders is also a concern, and obesity in elderly women was recorded at 60 percent while obesity in elderly men was 43.8 percent (De Silva et al 2017). According to the WHO, this dual burden of nutrition has a major impact on the ageing process, and on the morbidity and mortality of the aged population.…”
Section: Population Ageing and Challenges To Health Carementioning
confidence: 99%